Isolation of Organophosphate (Chlorpyrifos)-degrading Bacterium from Agricultural Farmlands in Batagarawa Local Government Area of Katsina State - Lawal, Babangida; Kareem, Bukola Lateefat; Adamu, Nafisa Abduljalil (Journal of Biochemistry, Microbiology and Biotechnology, 2024)
Chlorpyrifos being the most frequently used organophosphorus pesticide is a broad-spectrum insecticide The massive application of chlorpyrifos has led to the contamination of water and soil which disrupt the environmental quality as many of its derivatives were detected in various ecosystems. This study is to isolate chlorpyrifos-degrading bacteria from agricultural farmland in Batagarawa Local Government area of Katsina State. Two chlorpyrifos-degrading bacteria were isolated using dilution technique followed by selective enrichment on minimal medium with chlorpyrifos as sole carbon source from soil samples collected from an agricultural farmland in Batagarawa Local Government Area of Katsina State. The isolates were characterized by Gram staining and biochemical test using Vitek II automated machine. The strains A10, A12 and A13 were identified to be Pseudomonas spp. and Staphylococcus spp.